WAYS TO IMPROVE THE OPTIONAL TRAINING IN SECONDARY SCHOOLS BASED ON INTERNATIONAL EXPERIENCE. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes a system of optional training in mathematics on the basis of the experience of different countries.Approaches in the U.S., Japan, Finland, Russia and South Korea and the South Korean education system are studying and their peculiarities.Practical recommendations are made based on international experiments in Uzbekistan.